Optimization of light-weight concrete for 3D printing applications - Afiq Hasnim (Nanyang Technological University, 2020)
Lightweight aggregate concretes contain a different type of aggregates as the ones used in conventional concrete. The aggregates in lightweight concrete are generally lighter and has a lower density. Certain types of lightweight concrete may not even have any aggregates in them. Due to this, it could greatly change the characteristic and the possibility of the concrete mix to be used for printing applications. Therefore, this report will be focusing on the optimization of lightweight aggregates in concrete for 3D concrete printing. Only three types of lightweight aggregate will be used in this study and they are, cenosphere, perlite and EPS foam beads. Different mixtures containing different amounts lightweight aggregates at 20, 60 and 100 percent are made in comparison to the control concrete mix which contains 100 percent river sand as its aggregate. Test will be conducted on the different concrete mix at their fresh state and cured state at 28 days of age. Test such as the slump and slump flow test and rheology will be conducted on the fresh specimen to understand the specimen’s flowability and buildability characteristics and together with destructive tests such as the compressive test and flexural tests that will be conducted, the strengths of the different test mixtures can be determined. Results obtained by the tests conducted will provide us with a further understanding of how the amount of lightweight aggregates would affect the performance of the concrete mix for each of the different lightweight aggregates used. With the gathered data an optimal mix design could also be obtained that will be suitable for 3D printing applications.